Preparation method of composite hydrogel scaffold, composite hydrogel scaffold and application of composite hydrogel scaffold
The composite hydrogel scaffold prepared by magnetic field induction and radiation crosslinking technology solves the problem of difficulty in repairing the upper and lower bones of the cartilage in the prior art, improves the gap problem caused by material stacking, improves the effect of osteoarthritis treatment and reduces the difficulty of surgery.
Patent Information
- Application Number
- CN202510057883.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-14
AI Technical Summary
Existing hydrogel stents are difficult to take into account both the repair of supramolecular and subchondral bones in osteoarthritis treatment, and the gap problems caused by material stacking reduce the treatment effect and increase the difficulty of surgery.
The first hydrogel scaffold with superparamagnetic particles arranged in a concentration gradient is formed through magnetic field induction technology, and the radiation crosslinking technology is used to completely crosslink on its high concentration side and the low concentration side is not completely crosslinked. Combined with the interface crosslinking of the second hydrogel scaffold, a composite hydrogel scaffold is formed, solving the void problem caused by material stacking.
This method can not only adapt to the natural chemical component gradient of cartilage tissue, improve bone repair effect, but also reduce the difficulty of surgical implantation and enhance the feasibility of treatment.
Smart Images

Figure CN119857176A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomaterials, and in particular to a preparation method of a composite hydrogel scaffold, a composite hydrogel scaffold and applications thereof. Background Art
[0002] Osteoarthritis is a chronic joint disease that can cause damage to cartilage and surrounding tissues. Current studies have shown that hydrogels can be used to repair cartilage caused by osteoarthritis. Considering that cartilage tissue is formed by a multi-layer structure including the cartilage layer on the outer surface and the subchondral bone at the bottom, the treatment of osteoarthritis often requires simultaneous consideration of the treatment and repair of both the suprachondral bone (cartilage layer) and the subchondral bone.
[0003] The Chinese invention patent application with application number 2024106554692 and application name "Magnetic hydroxyapatite-based composite hydrogel scaffold and its preparation method and application" proposes a hydrogel scaffold for repairing subchondral bone. However, due to the different chemical compositions and distributions in the layers of subchondral bone, for example, hydroxyapatite has a natural chemical composition gradient in cartilage tissue, and the bone repair effect of the hydrogel scaffold prepared therefrom is limited. In view of the chemical gradient existing in cartilage tissue, different layers of cartilage tissue are currently mainly repaired by stacking different materials to adapt to the complex structure of cartilage tissue, which greatly increases the difficulty of cartilage tissue repair and reduces the treatment effect. At the same time, the stacking of multiple materials will also greatly increase the difficulty of surgery during implantation.
[0004] Furthermore, the suprachondral bone and subchondral bone have completely different compositions and therefore completely different properties, which also poses a great challenge to the design and use of repair implant materials. The current common solution is to implant two materials separately during bone treatment, that is, the upper layer uses a material that can promote suprachondral bone repair, and the lower layer uses a material that can support the regeneration and repair of subchondral bone. Although this solution can take into account the needs of upper and lower bone repair at the same time, the two materials are usually implanted in a simple stacking manner, and interfaces and gaps will inevitably be generated between the materials during use, which is extremely unfavorable for bone repair. At the same time, the separate implantation of the two materials also increases the difficulty of the operation and increases the risks faced during the operation, making it a major obstacle for hydrogel materials to move towards actual clinical application.
[0005] Therefore, there is an urgent need for a new type of hydrogel scaffold that can be used for bone treatment and a preparation method thereof, so that the prepared hydrogel scaffold can not only adapt to the natural chemical component gradient of cartilage tissue, but also improve the gap problem caused by material stacking, thereby improving the bone treatment and repair effect while reducing the difficulty of implantation and repair. Summary of the invention
[0006] In view of this, the embodiments of the present invention provide a method for preparing a composite hydrogel scaffold, a composite hydrogel scaffold and applications thereof, which can adapt to the chemical component gradient of cartilage tissue while solving the gap problem caused by material stacking to promote bone repair.
[0007] One aspect of the present invention provides a method for preparing a composite hydrogel scaffold, the method comprising the following steps: placing a specific mold containing a mixed solution containing a hydrogel precursor liquid and a plurality of superparamagnetic particles in an inhomogeneous magnetic field, driving the superparamagnetic particles in the mixed solution to be arranged in a concentration gradient in a set direction by a magnetic field induction technique, and irradiating the high-concentration side of the superparamagnetic particles in the mixed solution by a radiation cross-linking technique to obtain a first hydrogel scaffold in which the high-concentration side of the superparamagnetic particles is completely cross-linked and the low-concentration side of the superparamagnetic particles is not completely cross-linked; The hydrogel precursor liquid is added to the low concentration side of the superparamagnetic particles in a specific mold, and the added hydrogel precursor liquid is irradiated using radiation cross-linking technology to completely cross-link it, forming a second hydrogel scaffold that has interface cross-linking with the first hydrogel scaffold, and then demolding to obtain a composite hydrogel scaffold.
[0008] In some embodiments of the present invention, before forming the mixed solution, the method further comprises: performing drug loading treatment on the superparamagnetic particles; Before adding the hydrogel precursor liquid to the low concentration side of the superparamagnetic particles in the specific mold, the method further comprises: adding a drug to the added hydrogel precursor liquid; and Before placing the specific mold containing the mixed liquid in the inhomogeneous magnetic field, the method further comprises: defoaming the mixed liquid containing the hydrogel precursor liquid and a plurality of superparamagnetic particles.
[0009] In some embodiments of the present invention, the superparamagnetic particles are subjected to drug loading treatment, comprising: The superparamagnetic particles are immersed in a solution containing drugs, and after a set immersion time, centrifugation, washing and drying are performed to obtain superparamagnetic particles loaded with drugs.
[0010] In some embodiments of the present invention, the radiation cross-linking technique includes a photo cross-linking technique or a temperature cross-linking technique; For the photo-crosslinking technology, the wavelength of the radiation light is 100-500nm, and the radiation time is 0-3600s and not 0; for the temperature-crosslinking technology, the radiation temperature ranges from 0-100°C and not 0, and the radiation time is 0-3600s and not 0.
[0011] In some embodiments of the present invention, the superparamagnetic particles include magnetic nanoparticles with superparamagnetism, or hollow porous magnetic hydroxyapatite microsphere particles formed by hydroxyapatite particles and magnetic nanoparticles with superparamagnetism; wherein the magnetic nanoparticles with superparamagnetism include ferroferric oxide nanoparticles, ferric oxide nanoparticles, manganese ferrite nanoparticles or manganese oxide nanoparticles, the mass percentage of hydroxyapatite in the magnetic hydroxyapatite microsphere particles is 50-95%, the mass percentage of magnetic nanoparticles with superparamagnetism is 5-50%, and the particle size of the magnetic hydroxyapatite microsphere particles is 1nm-10μm.
[0012] In some embodiments of the present invention, the height of the second hydrogel scaffold is 1.5 to 2 mm; The ratio of the hydrogel precursor liquid to the superparamagnetic particles in the mixed solution is 1 mL: 0 to 15 mg and is not 0; and The inhomogeneous magnetic field is provided by NdFeB magnets or electromagnets.
[0013] Another aspect of the present invention provides a composite hydrogel scaffold, which is prepared by the preparation method described in any of the above embodiments, and includes a first hydrogel scaffold and a second hydrogel scaffold that is interfacially cross-linked with the first hydrogel scaffold; the first hydrogel scaffold includes a first hydrogel scaffold body, and superparamagnetic particles located inside the first hydrogel scaffold body and arranged in a concentration gradient in a set direction; wherein the superparamagnetic particles arranged in a concentration gradient are formed by placing a plurality of superparamagnetic particles in an inhomogeneous magnetic field and using a magnetic field induction technology; the first hydrogel scaffold is formed by radiating the high concentration side of the superparamagnetic particles using a radiation cross-linking technology; The second hydrogel scaffold is located on the low concentration side of the superparamagnetic particles of the first hydrogel scaffold.
[0014] In some embodiments of the present invention, the superparamagnetic particles and the second hydrogel scaffold are loaded with drugs to achieve sustained release of the drugs.
[0015] In some embodiments of the present invention, the radiation cross-linking technique includes a photo cross-linking technique or a temperature cross-linking technique; In the case where the radiation cross-linking technology is a photo cross-linking technology, the hydrogel precursor liquid includes a photoinitiator and a hydrogel polymer for photo cross-linking mixed in a set ratio; in the case where the radiation cross-linking technology is a temperature cross-linking technology, the hydrogel precursor liquid is a modified hydrogel polymer for temperature cross-linking; Among them, the hydrogel polymer used for photo-crosslinking includes glycidyl methacrylate-modified hyaluronic acid GMHA, silk fibroin, chitosan or agarose; and the modified hydrogel polymer used for temperature crosslinking includes poly (N-isopropylacrylamide) or chitosan.
[0016] Another aspect of the present invention provides an application of a composite hydrogel scaffold prepared by the preparation method described in any of the above embodiments for cartilage repair in bone treatment or for observation of the repair status of a bone treatment implantation site by nuclear magnetic resonance imaging.
[0017] The present invention proposes a preparation method of a composite hydrogel scaffold, a composite hydrogel scaffold and an application thereof, which utilizes a magnetic field induction technology to form a first hydrogel scaffold in which superparamagnetic particles are arranged in a concentration gradient to adapt to the natural chemical component gradient in cartilage tissue, and controls the radiation cross-linking technology to obtain a second hydrogel scaffold that has an interface cross-linking with the first hydrogel scaffold to improve the gaps and friction caused by material stacking, thereby improving the bone treatment and repair effect while reducing the difficulty of surgical implantation of the repair material.
[0018] Additional advantages, purposes, and features of the present invention will be described in part in the following description, and will become apparent to those skilled in the art after studying the following, or may be learned from the practice of the present invention. The purposes and other advantages of the present invention may be achieved and obtained by the structures specifically indicated in the specification and the accompanying drawings.
[0019] Those skilled in the art will appreciate that the objectives and advantages that can be achieved with the present invention are not limited to the above specific description, and the above and other objectives that can be achieved by the present invention will be more clearly understood from the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute a limitation of the present invention. In the drawings: Figure 1 Schematic diagram of the process of preparing a hydrogel with a concentration gradient by a stacking method in one embodiment of the present invention.
[0021] Figure 2 The figure is a schematic diagram of a process for preparing a composite hydrogel scaffold according to an embodiment of the present invention.
[0022] Figure 3 Schematic diagram of a composite hydrogel scaffold in one embodiment of the present invention.
[0023] Figure 4 This is a comparison chart of the bone repair effect of the composite hydrogel scaffold in one embodiment of the present invention. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and the accompanying drawings. Here, the illustrative embodiments of the present invention and their descriptions are used to explain the present invention, but are not intended to limit the present invention.
[0025] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the solutions according to the present invention are shown in the accompanying drawings, while other details that are not closely related to the present invention are omitted.
[0026] It should be emphasized that the term “include / comprises” when used herein refers to the presence of features, elements, steps or components, but does not exclude the presence or addition of one or more other features, elements, steps or components.
[0027] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. In the accompanying drawings, the same reference numerals represent the same or similar components, or the same or similar steps.
[0028] Since cartilage tissue has a natural chemical composition gradient, hydrogel materials with a concentration gradient can be used to treat osteoarthritis. Currently, one of the commonly used methods for preparing hydrogels with a concentration gradient is the stacking method. This method does not require additional equipment. It only requires the preparation of prefabricated liquids with different solute concentrations to prepare each layer of hydrogel material. The material with a preset structure can be obtained by stacking layer by layer. The preparation process is as follows: Figure 1 However, the hydrogel prepared by the stacking method easily produces interfaces and gaps between the stacked layers, which not only limits the repair effect but also increases the difficulty of surgery.
[0029] Considering the position of the upper and lower bones of the cartilage during the treatment of osteoarthritis and their respective requirements for materials, the present application designs a composite hydrogel scaffold (Composite Hydrogel Scaffold, CHS) and its preparation method. Before gel formation (i.e., cross-linking and curing), an external magnetic field is used to induce the superparamagnetic particles in the hydrogel precursor liquid (or hydrogel precursor solution) to form a concentration gradient, and the first hydrogel scaffold is formed by an improved cross-linking method, which solves the problem that the regeneration of the cartilage layer in the cartilage tissue will be affected by the gradient of chemical components such as hydroxyapatite; at the same time, the present application also adds a second hydrogel scaffold with an interface cross-linking with the first hydrogel scaffold on one side of the first hydrogel scaffold that is completely cross-linked on the high concentration side of the superparamagnetic particles and the low concentration side of the superparamagnetic particles (which can be set relative to the high concentration side of the superparamagnetic particles) is not completely cross-linked, so as to improve the gap problem caused by the stacking of different repair materials for the upper and lower cartilage bones. Through the above process, a new type of composite hydrogel scaffold with a concentration gradient can be prepared, which can be used for the treatment and repair of osteoarthritis. In addition, the composite hydrogel scaffold prepared in the present application can achieve a good cartilage repair effect while providing the function of real-time observation of the hydrogel scaffold implantation status using magnetic resonance imaging (MRI, also known as magnetic resonance imaging).
[0030] Concentration gradient is a phenomenon that exists widely in nature. It represents the difference in the concentration of solutes or dispersed particles in space. For example, oxygen and ATP inside cells, the migration of white blood cells during inflammation, and the migration of sperm during egg fertilization or embryonic development are all caused by concentration gradients. In addition to concentration gradients in solutions, concentration gradients also occur in "solid environments" in nature. For example, spatial differences in the degree of mineralization and the amount of collagen play a central role in tissue structures, such as tendons, human dentin and cartilage. This gradient plays a mediating role between materials of different moduli and has significant resistance to crack propagation and contact deformation. Based on this concept, researchers have designed and prepared many new composite materials, which are generally called "concentration gradient materials."
[0031] The novel composite hydrogel scaffold proposed in the present application can be divided into two parts: a first hydrogel scaffold (including a first hydrogel scaffold body and a plurality of superparamagnetic particles) and a second hydrogel scaffold. Considering that the concentration gradient of the hydrogel material itself is difficult to control, and previous studies have shown that magnetic particles help promote cartilage growth, in order to adapt to the natural chemical component gradient present in the subchondral bone, the present application can use magnetic field induction technology to make the first hydrogel scaffold used to promote subchondral bone repair contain superparamagnetic particles with a concentration gradient; and the second hydrogel scaffold does not contain superparamagnetic particles, and only uses hydrogel materials to promote supracandricular bone repair. That is, the first hydrogel scaffold can be prepared from a mixture of a hydrogel precursor fluid and a plurality of superparamagnetic particles, and the first hydrogel scaffold can be prepared only from a hydrogel precursor fluid. In addition, through an improved cross-linking method, the present application can establish an interface cross-linking between the first hydrogel scaffold and the second hydrogel scaffold, thereby reducing the difficulty of surgery while taking into account the repair of the upper and lower bones of the cartilage.
[0032] In some embodiments of the present invention, the present invention combines the advantages of the stacking method and the magnetic field induction method to design an improved method for preparing a composite hydrogel scaffold capable of forming a concentration gradient, and the method may include the following steps: A specific mold containing a mixed liquid (or a mixed suspension) containing a hydrogel precursor liquid and a plurality of superparamagnetic particles is placed in an inhomogeneous magnetic field, and the superparamagnetic particles in the mixed liquid are driven to arrange in a concentration gradient in a set direction by a magnetic field induction technique, and the high concentration side of the superparamagnetic particles in the mixed liquid is irradiated by a radiation cross-linking technique to obtain a first hydrogel scaffold in which the high concentration side of the superparamagnetic particles is completely cross-linked and the low concentration side of the superparamagnetic particles is not completely cross-linked; the hydrogel precursor liquid is added to the low concentration side of the superparamagnetic particles in the specific mold, and the added hydrogel precursor liquid is irradiated by a radiation cross-linking technique to make it completely cross-linked, forming a second hydrogel scaffold having an interface cross-linking with the first hydrogel scaffold, thereby obtaining a composite hydrogel scaffold.
[0033] Specifically, the process of the method for preparing the composite hydrogel scaffold described in any of the above embodiments is as follows: Figure 2 As shown, a hydrogel precursor liquid and a plurality of superparamagnetic particles are mixed and the mixed liquid is added to a specific mold; an external magnetic field source is used to provide an inhomogeneous magnetic field, and after the specific mold loaded with the mixed liquid is placed in the inhomogeneous magnetic field, the superparamagnetic particles in the mixed liquid are subjected to the force of the magnetic field (due to different magnetic field strengths at different positions) and move in the uncrosslinked mixed liquid, thereby being arranged in a concentration gradient in a set direction; after the arrangement of the superparamagnetic particles reaches the expected state, an external radiation source can be used to irradiate the high concentration side of the superparamagnetic particles, and a first hydrogel scaffold is obtained by crosslinking and curing, in which the high concentration side of the superparamagnetic particles is completely crosslinked and the low concentration side of the superparamagnetic particles is not completely crosslinked. A hydrogel precursor liquid is added to the low concentration side of the superparamagnetic particles of the first hydrogel scaffold (the hydrogel precursor liquid is added to a specific mold). Since a large number of uncrosslinked bonds may exist on the low concentration side of the superparamagnetic particles in the first hydrogel scaffold at this time, crosslinking and curing can be performed by radiation crosslinking technology, and finally demolding is performed to obtain the composite hydrogel scaffold of the present application. That is, the composite hydrogel scaffold proposed in the present application may include a first hydrogel scaffold and a second hydrogel scaffold having an interface cross-linking with the first hydrogel scaffold. The first hydrogel scaffold includes a first hydrogel scaffold body, and superparamagnetic particles located inside the first hydrogel scaffold body and arranged in a concentration gradient in a set direction; the second hydrogel scaffold is located on the low concentration side of the superparamagnetic particles of the first hydrogel scaffold.
[0034] Specifically, for a mixed liquid formed by a magnetic component and a hydrogel precursor liquid, an external magnetic field can be used to control the movement of the magnetic component to affect the arrangement of the magnetic particles, thereby realizing the preparation of a concentration gradient material, that is, a magnetic field induction method can be used to prepare a hydrogel with a concentration gradient. Therefore, the present application can place a number of superparamagnetic particles in an inhomogeneous magnetic field, and use magnetic field induction technology to control the movement of the superparamagnetic particles so that the superparamagnetic particles are arranged in a concentration gradient. After the arrangement of the superparamagnetic particles reaches the expected level, a cross-linking method can be used to cross-link the hydrogel so that the hydrogel is partially formed (forming a first hydrogel scaffold in which the high-concentration side of the superparamagnetic particles is completely cross-linked and the low-concentration side of the superparamagnetic particles is not completely cross-linked). At this time, the superparamagnetic particles can be fixed by the first hydrogel scaffold and no longer move. The composite hydrogel scaffold proposed in the present application can be as follows Figure 3 In addition, the standing time of the mixed solution used to prepare the first hydrogel scaffold in the non-uniform magnetic field in the present application needs to be determined according to various factors such as the magnetic field strength, for example, the standing time can be 2 minutes, 5 minutes or 30 minutes, etc., and the present application does not make specific limitations thereon.
[0035] As an example, the non-uniform magnetic field during magnetic field induction in the present application is provided by a neodymium iron boron magnet or an electromagnet. For example, a neodymium iron boron magnet can be placed on any side of a specific mold (loaded with a mixture of a hydrogel precursor fluid and a plurality of superparamagnetic particles), so that the superparamagnetic particles in the specific mold move due to the different magnetic field strengths at different locations of the non-uniform magnetic field. The above is only an example. The present application does not specifically limit the external magnetic field source that provides a non-uniform magnetic field. Any magnetic field source that can provide a non-uniform magnetic field is suitable for the magnetic field induction of the present application. In the present application, the concentration of superparamagnetic particles at each position may be the same as the concentration at the corresponding position in the cartilage tissue, or it may be different, so as to form a concentration gradient arrangement.
[0036] In some embodiments of the present invention, the superparamagnetic particles are magnetic particles with superparamagnetism, such as ferroferric oxide particles, ferrous oxide particles, manganese ferrite particles or manganese oxide particles. The superparamagnetic particles arranged in a concentration gradient in the present application can be composed of any substance with superparamagnetism. The above-mentioned ferroferric oxide is only an example, and the present invention is not limited thereto. Moreover, in order to facilitate the regulation of the arrangement position of the particles by an external non-uniform magnetic field, the superparamagnetic particles can be nano-sized particles, for example, the particle size range of the superparamagnetic particles of the present application can be 1 to 100 nm. In addition, there is a concentration gradient of hydroxyapatite in the subchondral bone. In order to conform to the current composition of cartilage tissue as much as possible, the superparamagnetic particles in the present application can be hollow porous magnetic hydroxyapatite microsphere particles formed by hydroxyapatite particles and magnetic nanoparticles with superparamagnetism. The present application does not specifically limit the preparation method of magnetic hydroxyapatite microsphere particles, which can be obtained by existing preparation technology, for example, co-precipitation method or biomineralization method can be used. The mass percentage of hydroxyapatite in the magnetic hydroxyapatite microsphere particles can be 50-95%, the mass percentage of magnetic nanoparticles with superparamagnetism in the magnetic hydroxyapatite microsphere particles can be 5-50%, and the magnetic hydroxyapatite microsphere particles have a spherical or quasi-spherical structure, and the particle size can be 1nm-10μm. In order to ensure the effect of subsequent bone repair, the superparamagnetic particles in the present application can use magnetic materials with good biocompatibility.
[0037] As an example, the cross-linking method in this application can be radiation cross-linking technology, or other existing cross-linking methods. Since the composite hydrogel scaffold prepared in this application is used for bone repair, in order to accurately regulate the hydrogel components to promote cartilage regeneration, this application can use radiation cross-linking technology that has little effect on the components and materials of the hydrogel scaffold to shape the hydrogel. The following description takes radiation cross-linking technology as an example.
[0038] In some embodiments of the present invention, in order to achieve the subsequent preparation of a second hydrogel scaffold that has an interface crosslink with the first hydrogel scaffold, the present application can use radiation crosslinking technology to irradiate the high concentration side of the superparamagnetic particles, so that the high concentration side of the superparamagnetic particles in the first hydrogel scaffold is completely crosslinked and the low concentration side of the superparamagnetic particles is not completely crosslinked. This is because the higher the radiation energy at the position closest to the radiation source, the faster the gel formation speed. When irradiating from the high concentration side of the superparamagnetic particles, there may be more uncrosslinked hydrogen bonds, free radicals or ions on the low concentration side of the superparamagnetic particles. When the hydrogel precursor fluid is added to the low concentration side of the superparamagnetic particles to prepare the second hydrogel scaffold, it is easy to achieve crosslinking between the interface of the added hydrogel precursor fluid and the first hydrogel scaffold.
[0039] Furthermore, radiation cross-linking technology can utilize various radiations to initiate cross-linking reactions between long polymer chains, including light radiation, gamma-ray radiation, or temperature radiation. If the present application adopts the photo-crosslinking technology, in the process of forming the first hydrogel scaffold, a light-transmissive specific mold for loading a mixed solution including a hydrogel precursor liquid and a plurality of superparamagnetic particles is required to be used so that the radiated light can be radiated on the high concentration side of the superparamagnetic particles (for example, the specific mold uses a light-transmissive material on the opposite sides in the set direction), and the radiation source used can be a light source (such as an ultraviolet light source or other light sources), and at this time the hydrogel precursor liquid can include a photoinitiator and a hydrogel polymer for photo-crosslinking mixed in a set ratio; if the temperature crosslinking technology is used, in the crosslinking process of the first hydrogel scaffold, the specific mold for loading a mixed solution including a hydrogel precursor liquid and a plurality of superparamagnetic particles cannot be prepared with a heat-insulating material, and the specific mold must be prepared with a material that can transfer heat, and the radiation source is a heat source. At this time, the hydrogel precursor liquid can be a modified hydrogel polymer for temperature crosslinking, for example, the hydrogel precursor liquid can be a precursor solution of a thermosensitive hydrogel; if the γ-ray radiation technology is used, the specific mold must be prepared with a material that can penetrate γ-rays. In addition, the present application does not specifically limit the shape of a particular mold, which can be determined according to the treatment method and treatment effect.
[0040] As an example, the set ratio of the photoinitiator and the hydrogel polymer in the hydrogel precursor liquid can be 0 to 30% wt and not 0. The photoinitiator is used to generate free radicals or cations based on radiation light in the ultraviolet light region or the visible light region, thereby initiating the polymerization and cross-linking of monomers. The compound may include lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (Lithium Phenyl (2,4,6-trimethylbenzoyl) phosphinate, LAP) or photoinitiator I2959, etc. The present invention does not specifically limit the material type of the photoinitiator, which can be any substance with photoinitiating properties. In addition, the hydrogel polymer mentioned in this application represents an intermediate before the cross-linking and curing of the hydrogel, which can be used to form a hydrogel. The hydrogel polymer used for photo-crosslinking includes polymer materials such as glycidyl methacrylate-modified hyaluronic acid (GMHA), silk fibroin, chitosan or agarose that can form a hydrogel by photo-crosslinking, and the modified hydrogel polymer used for temperature-crosslinking may include poly-N-isopropylacrylamide or chitosan, etc. The specific materials of the hydrogel polymer used for photo-crosslinking and the hydrogel polymer used for temperature-crosslinking mentioned above are only examples, and the present invention is not limited thereto.
[0041] In some embodiments of the present invention, for the photo-crosslinking technology, the wavelength of the irradiated light may be 100-500nm, and the irradiation time may be 0-3600s and not 0. For example, the present application may use ultraviolet light of 100-400nm as the irradiation light source for irradiation, and may also use visible light of 400-500nm as the irradiation light source (for example, blue light with a wavelength of 405nm), and the irradiation time may be 30s, 60s, 2min, 5min, 15min, 30min, 1h, 1.5h or 2h, etc. For the temperature crosslinking technology, the irradiation temperature ranges from 0 to 100°C and is not 0, and the irradiation time is 0 to 3600s and is not 0. For example, the irradiation temperature may be 50°C, 60°C, 80°C or 100°C, etc., and the irradiation time may be 30s, 60s, 2min, 5min, 15min, 30min, 1h, 1.5h or 2h, etc.
[0042] As an example, in order to use the composite hydrogel scaffold prepared in the present application for repairing suprachondral bone, the height of the second hydrogel scaffold in the composite hydrogel scaffold can be designed to be 1.5 to 2 mm. The height of the second hydrogel scaffold mentioned above is only an example, which can be set according to individual differences, or based on the height ratio of the first hydrogel scaffold and the second hydrogel scaffold, and the present invention is not limited thereto. For example, according to the specific circumstances of the required repair site and the defect, the height of the second hydrogel scaffold can be 2 mm, 1.7 mm and 1.5 mm, respectively. Further, although the first hydrogel scaffold body and the second hydrogel scaffold can both be formed by a hydrogel precursor liquid, the hydrogel precursor liquid used to prepare the first hydrogel scaffold and the hydrogel precursor liquid used to prepare the second hydrogel scaffold can be made of different components, and the first hydrogel scaffold and the second hydrogel scaffold can be cured by using radiation cross-linking technology. Different radiation methods can be used, even if the first hydrogel scaffold and the second hydrogel scaffold are cross-linked using the same radiation method, different radiation parameters can also be used, and the present invention does not specifically limit it.
[0043] In some embodiments of the present invention, superparamagnetic particles and the second hydrogel scaffold are loaded with drugs to achieve sustained release of drugs. The drugs loaded in the superparamagnetic particles and the second hydrogel scaffold may be different. The superparamagnetic particles are loaded with drugs for promoting subchondral bone regeneration, such as vascular endothelial growth factor (VEGF); the second hydrogel scaffold is loaded with drugs for promoting suprachondral bone regeneration, such as metformin. The above-mentioned drug types are only examples, and other types of drugs may also be used. Drug loading can be performed based on the purpose of the composite hydrogel scaffold. In addition, the hollow porous structure of the magnetic hydroxyapatite microsphere particles is conducive to the loading and sustained release of drugs.
[0044] For example, the first hydrogel scaffold in the composite hydrogel scaffold mentioned in the present application can be a hydrogel material that combines superparamagnetic hydroxyapatite microsphere particles with GMHA. Studies have shown that this material can play a good role in repairing subchondral bone, and on this basis promote cartilage tissue repair, and has a positive effect on the treatment of osteoarthritis. Figure 4 As shown, compared with the composite hydrogel scaffold with uniformly arranged superparamagnetic particles proposed in the application number 2024106554692 and the application name "Magnetic Hydroxyapatite-based Composite Hydrogel Scaffold and Its Preparation Method and Application", the hydrogel scaffold proposed in this application has a better repair effect within the same bone repair cycle, and the score of the ICRS (International Cartilage Repair Society) scoring system is also higher, that is, this application is based on the design of realizing concentration gradient in the same material system, which can be more helpful for the repair of cartilage tissue and the treatment of osteoarthritis. In addition, the composite hydrogel scaffold of this application can also realize in situ MRI monitoring of the affected area, which can better realize the evaluation of the treatment effect.
[0045] As an example, Figure 2 In the method, a NdFeB magnet can be set as an external magnetic field source at the bottom of a specific mold, and a high concentration side of superparamagnetic particles can be formed on the side close to the NdFeB magnet; and when a hydrogel precursor liquid is added to prepare a second hydrogel scaffold, an external radiation source can be set at the top of the specific mold for radiation, so that the second hydrogel scaffold is formed. A composite hydrogel scaffold can also be prepared by the following radiation method: an external magnetic field source is set at the top of a specific mold, and a mixed liquid in the specific mold can form a concentration gradient with a gradually decreasing concentration from top to bottom. At this time, an external radiation source is set at the top of the specific mold, and a first hydrogel scaffold with a high concentration side of superparamagnetic particles completely cross-linked and a low concentration side of superparamagnetic particles not completely cross-linked is obtained by cross-linking and curing, the first hydrogel scaffold is demoulded and placed in another mold, and a hydrogel precursor liquid is added to the low concentration side of the superparamagnetic particles of the first hydrogel scaffold, and a composite hydrogel scaffold is obtained after cross-linking and curing. In addition, the first hydrogel scaffold and the second hydrogel scaffold can be separately manufactured, assembled together and cross-linked at the interface through radiation cross-linking technology. For example, the radiation time can be minimized to allow the first hydrogel scaffold and the second hydrogel scaffold to be initially formed (i.e., the high-concentration side of the superparamagnetic particles in the first hydrogel scaffold is completely cross-linked and the low-concentration side of the superparamagnetic particles is not completely cross-linked; one side of the second hydrogel scaffold is completely cross-linked, while the other side is not completely cross-linked), and then the two are stacked and irradiated again to achieve interface cross-linking.
[0046] As an example, the mixing ratio of the hydrogel precursor liquid and the superparamagnetic particles is 1 mL: 0-15 mg and is not 0 (for example, the mixing ratio can be 5 mg / mL, 8 mg / mL, 10 mg / mL or 15 mg / mL, etc.), and before the mixed liquid including the hydrogel precursor liquid and a plurality of superparamagnetic particles is placed in an inhomogeneous magnetic field, the mixed liquid needs to be defoamed. In order to accurately control the bone repair effect of the hydrogel scaffold, a physical defoaming treatment method without introducing other chemical components can be adopted, such as standing, vacuuming or ultrasound.
[0047] In some embodiments of the present invention, before forming the mixed suspension, the method further includes: performing drug loading treatment on the superparamagnetic particles; and before adding the hydrogel precursor liquid to the low concentration side of the superparamagnetic particles of the first hydrogel scaffold, the method further includes: adding drugs to the added hydrogel precursor liquid. Specifically, the process of drug loading treatment of superparamagnetic particles can be specifically as follows: soaking the superparamagnetic particles in a solution containing drugs, centrifuging, washing and drying after a set soaking time to obtain drug-loaded superparamagnetic particles. Wherein, the soaking time is set to be no more than 72h. The steps for drug loading of the hydrogel precursor liquid used to prepare the second hydrogel scaffold are as follows: add a set amount of drug to the hydrogel precursor liquid used to prepare the second hydrogel scaffold, and stir to dissolve it.
[0048] In a specific embodiment of the present invention, the superparamagnetic particles are hollow porous magnetic hydroxyapatite microsphere particles, the hydrogel polymer used to prepare the first hydrogel scaffold and the second hydrogel scaffold is GMHA that can be photocrosslinked, the photoinitiator is LAP, and the preparation steps are as follows: (1) According to the concentration standard of 5 mg / mL, 0.25 mg of magnetic hydroxyapatite microsphere particles were added to 500 μL of hydrogel precursor solution including GMHA and LAP to form a mixed suspension; (2) After the mixed suspension was defoamed by ultrasound, it was added to a PMMA (Poly(methyl methacrylate)) cylindrical spherical ... (3) after the concentration distribution of the magnetic hydroxyapatite microsphere particles reaches the expected level, the external magnetic field source is removed, and the bottom of the mold is irradiated with an ultraviolet radiation source for 1 min; (4) after the irradiation is completed, the ultraviolet radiation source is removed, and a hydrogel precursor liquid including GMHA and LAP is added to the top of the mold, and its height is controlled to be 1.5 to 2 mm, and an ultraviolet radiation source is placed on the top of the mold for irradiation for 1 min; (5) after the irradiation is completed, the mold is demolded to obtain a composite hydrogel scaffold with a concentration gradient.
[0049] The composite hydrogel scaffold and preparation method thereof proposed in this application have the following advantages: (1) The new process has the advantages of combining the magnetic field induction method and the stacking method to prepare a concentration gradient composite hydrogel scaffold. At the same time, it eliminates the possible gaps between the pure GMHA hydrogel and the underlying composite hydrogel scaffold, reducing the potential impact of the interfacial gap on the performance of the concentration gradient composite hydrogel scaffold.
[0050] (2) Compared with the overall uniform composite hydrogel scaffold, the composite hydrogel scaffold with concentration gradient proposed in the present application still contains a certain amount of superparamagnetic particles on the low concentration side of superparamagnetic particles, but its concentration is much lower than that of the uniform composite hydrogel scaffold, especially under the condition that there is a second hydrogel scaffold with the same thickness as the cartilage layer and does not contain any superparamagnetic particles. In theory, the effect of superparamagnetic particles on cartilage repair has been weakened to the greatest extent.
[0051] (3) The first hydrogel scaffold and the second hydrogel scaffold can be specifically loaded with drugs that promote cartilage repair, and the loaded drugs can act independently on their respective target treatment areas, thereby achieving the best treatment effect.
[0052] The present application proposes an application of a composite hydrogel scaffold described in any of the above embodiments or a composite hydrogel scaffold prepared by the preparation method described in any of the above embodiments for use in cartilage repair in bone treatment or for use in observing the repair status of a bone treatment implantation site through nuclear magnetic resonance imaging.
[0053] It should be clear that the present invention is not limited to the specific configuration and processing described above and shown in the figures. For the sake of simplicity, a detailed description of the known method is omitted here. In the above embodiments, several specific steps are described and shown as examples. However, the method process of the present invention is not limited to the specific steps described and shown, and those skilled in the art can make various changes, modifications and additions, or change the order between the steps after understanding the spirit of the present invention.
[0054] In the present invention, features described and / or illustrated for one embodiment may be used in the same or similar manner in one or more other embodiments, and / or combined with or replace features of other embodiments.
[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the embodiments of the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite hydrogel scaffold, characterized in that: The method comprises the following steps: A specific mold containing a mixture containing a hydrogel precursor liquid and a plurality of superparamagnetic particles is placed in an inhomogeneous magnetic field, the superparamagnetic particles in the mixture are driven to arrange in a concentration gradient in a set direction by a magnetic field induction technique, and a radiation cross-linking technique is used to irradiate the high-concentration side of the superparamagnetic particles in the mixture to obtain a first hydrogel scaffold in which the high-concentration side of the superparamagnetic particles is completely cross-linked and the low-concentration side of the superparamagnetic particles is not completely cross-linked; The hydrogel precursor liquid is added to the low concentration side of the superparamagnetic particles in a specific mold, and the added hydrogel precursor liquid is irradiated using a radiation cross-linking technique to completely cross-link it, thereby forming a second hydrogel scaffold that has an interface cross-linking with the first hydrogel scaffold, and then demolding is performed to obtain a composite hydrogel scaffold.
2. The preparation method according to claim 1, characterized in that: Before forming the mixed solution, the method further comprises: performing drug loading treatment on the superparamagnetic particles; Before adding the hydrogel precursor liquid to the low concentration side of the superparamagnetic particles in the specific mold, the method further comprises: adding a drug to the added hydrogel precursor liquid; and Before placing the specific mold containing the mixed liquid in the inhomogeneous magnetic field, the method further comprises: defoaming the mixed liquid containing the hydrogel precursor liquid and a plurality of superparamagnetic particles.
3. The preparation method according to claim 2, characterized in that: The drug loading treatment of the superparamagnetic particles comprises: The superparamagnetic particles are immersed in a solution containing drugs, and after a set immersion time, centrifugation, washing and drying are performed to obtain superparamagnetic particles loaded with drugs.
4. The preparation method according to claim 1, characterized in that: The radiation cross-linking technology includes light cross-linking technology or temperature cross-linking technology; For the photo-crosslinking technology, the wavelength of the radiation light is 100-500nm, and the radiation time is 0-3600s and not 0; for the temperature-crosslinking technology, the radiation temperature ranges from 0-100°C and not 0, and the radiation time is 0-3600s and not 0.
5. The preparation method according to claim 1, characterized in that: The superparamagnetic particles include magnetic nanoparticles with superparamagnetism, or hollow porous magnetic hydroxyapatite microsphere particles formed by hydroxyapatite particles and magnetic nanoparticles with superparamagnetism; The magnetic nanoparticles with superparamagnetism include ferroferric oxide nanoparticles, ferrous oxide nanoparticles, manganese ferrite nanoparticles or manganese oxide nanoparticles, the mass percentage of hydroxyapatite in the magnetic hydroxyapatite microsphere particles is 50-95%, the mass percentage of the magnetic nanoparticles with superparamagnetism is 5-50%, and the particle size of the magnetic hydroxyapatite microsphere particles is 1nm-10μm.
6. The preparation method according to claim 1, characterized in that: The height of the second hydrogel scaffold is 1.5 to 2 mm; the ratio of the hydrogel precursor liquid to the superparamagnetic particles in the mixed solution is 1 mL: 0 to 15 mg and is not 0; and The non-uniform magnetic field is provided by a neodymium iron boron magnet or an electromagnet.
7. A composite hydrogel scaffold, characterized in that: The composite hydrogel scaffold is prepared by the preparation method according to any one of claims 1 to 6, comprising a first hydrogel scaffold and a second hydrogel scaffold having an interface cross-linking with the first hydrogel scaffold; The first hydrogel scaffold comprises a first hydrogel scaffold body, and superparamagnetic particles located inside the first hydrogel scaffold body and arranged in a concentration gradient in a set direction; wherein the superparamagnetic particles arranged in a concentration gradient are formed by placing a plurality of superparamagnetic particles in an inhomogeneous magnetic field using a magnetic field induction technique; the first hydrogel scaffold is formed by irradiating a high concentration side of the superparamagnetic particles using a radiation cross-linking technique; The second hydrogel scaffold is located on the low-concentration side of the superparamagnetic particles of the first hydrogel scaffold.
8. The composite hydrogel scaffold according to claim 7, characterized in that: The superparamagnetic particles and the second hydrogel scaffold are loaded with drugs to achieve sustained release of the drugs.
9. The composite hydrogel scaffold according to claim 8, characterized in that: The radiation cross-linking technology includes light cross-linking technology or temperature cross-linking technology; In the case where the radiation crosslinking technology is a photocrosslinking technology, the hydrogel precursor liquid includes a photoinitiator and a hydrogel polymer for photocrosslinking mixed in a set ratio; in the case where the radiation crosslinking technology is a temperature crosslinking technology, the hydrogel precursor liquid is a modified hydrogel polymer for temperature crosslinking; Wherein, the hydrogel polymer for photo-crosslinking includes glycidyl methacrylate-modified hyaluronic acid GMHA, silk fibroin, chitosan or agarose; and the modified hydrogel polymer for temperature-crosslinking includes poly (N-isopropylacrylamide) or chitosan.
10. An application of the composite hydrogel scaffold prepared by the preparation method according to any one of claims 1 to 6 for cartilage repair in bone treatment or for observation of repair conditions at a bone treatment implantation site by nuclear magnetic resonance imaging.
Citation Information
Patent Citations
High-strength continuous gradient composite scaffold and preparation method thereof
CN102861361A
Continuous gradient composite scaffold and preparation method thereof
CN102861362A
Cartilage-bone repair support with bionic gradient and preparation method thereof
CN109481736A
Double-layer bone-cartilage repair bracket and preparation method thereof
CN110404108A
Preparation method of photo-crosslinking 4D IPN magnetic response cartilage repair gradient hydrogel
CN115177792A